Mindfulness Therapy in Learning to Reduce Aggressive Behavior among Children at TKN 01 Dompu - Asnih Sari; Ihlas; Muslim (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of mindfulness therapy within the learning process as a strategy for addressing aggressive behavior among children at TKN 01, Dompu District. Aggressive behavior in early childhood may interfere with children's social interactions, emotional regulation, and participation in classroom learning. Therefore, learning activities that encourage self-awareness and emotional regulation are considered important in supporting children's socio-emotional development. This study employed a qualitative descriptive approach involving 12 participants, consisting of 10 children and 2 classroom teachers at TKN 01, Dompu District. Data were collected through classroom observations, semi-structured interviews with teachers, and documentation of learning activities. The data were analyzed using the stages of data reduction, data display, and conclusion drawing to identify patterns related to the implementation of mindfulness therapy in classroom learning. The findings indicate that mindfulness therapy was integrated into daily learning through breathing exercises, relaxation activities, focused attention, and guided emotional reflection. Teachers consistently facilitated these activities to help children recognize, express, and regulate their emotions in appropriate ways. Based on teachers' observations and classroom documentation, children demonstrated improved emotional awareness, greater self-control, more positive peer interactions, and fewer observable incidents of aggressive behavior during learning activities. These findings suggest that the implementation of mindfulness therapy within classroom learning provides a supportive approach for fostering emotional regulation and promoting positive social behavior among young children in early childhood education settings.